Clay as a potential parasite cleanse in the light of Islamic perspective - Mat Yusof, Afzan; Barudin, Mohd Aiman; Md. Isa, Muhammad Lokman (IIUM Press, International Islamic University Malaysia, 2017)
Clay minerals are used for therapeutic purposes, with a beneficial effect on health especially in pharmaceutical formulations in the form of administered topically such as for dermatological protectors and cosmetics due to its high specific area and absorption capacity. It is commonly used for aesthetic medicine due to its cation exchange capacity, cooling index and useful for treating dermatological diseases, pain alleviation of chronic rheumatic inflammations, clean, moisturise skin, combat compact lipodystrophies, acne and cellulite. Currently, many scholars tried to achieve an understanding of the hadith scriptures on the subject in the advent of modern science, but normally misleading interpretation happened due to some researchers did not follow the flow of hadith science (ulum al-hadith) methodology by which to correlate ahadith with recent scientific findings. Some of the hadith texts are still beyond explanation, awaiting further scientific advancements in order to avoid misinterpretation of hadith text. An authentic hadith narrated by Imam Muslim in his Sahih Muslim book (Sahih Muslim, vol 5, hadith no. 522) as Prophet said; “…the whole world has been made a place of prayer for us, and its soil has been made a purification for us when we do not find water”. This hadith can be a sign of revealed proof in our Deen that clay can be used as a tool to clean either physically or spiritually, whereby can be potentially used as a parasite cleanse as explained further in this article. Here, in this article, search of ahadith correspond to clay is generally used as a methodological framework along with other supportive explanation from Islamic jurisprudence so that these revealed facts can be an additional value for strengthening the Islamic tradition of scientific knowledge in this modern time pertaining to application of hadith to uncover the importance of clay as a potential for a parasitecleanse for human use.